Public Policy Implementation Effectiveness (Case Study Of Village Fund Implementation In Linggo Pasuruan) - Aminullah Aminullah; A. Juli Andi Gani; Suryadi Suryadi; Bambang Santoso Hariyono (Wacana Journal of Social and Humanity Studies, 2022)
Overview of this research, researchers try to understand the phenomenon of empirical gaps/reality, theorists, and normative problems village fund implementation from portraits Process effectiveness Implementation Research method using qualitative research types sourced from human instruments, events, and documents. Data collection techniques with an in-depth interview, observation, and documentation. While the data analysis used is interactive model data analysis initiated by Miles Huberman, and Saldana (2014). The results of this study revealed that, in the process of implementing village funds in general based on the fact in the field that it is already running, but there are still many weaknesses found ranging from communication between actors that have not been maximal or even socialization related to village funds are very minimally carried out by the Village Government to the Community, in addition to the Government Apparatus Resources at the beginning of the year the implementation of the Village Fund program still requires adaptation to existing laws and regulations. So the objectives of the Village Fund have not been achieved maximally.